Trimodality therapy for atypical teratoid/rhabdoid tumor is associated with improved overall survival: A surveillance, epidemiology, and end results analysis. Issue 12 (28th August 2019) - Quinn, Thomas J.; Almahariq, Muayad F.; Siddiqui, Zaid A.; Thompson, Andrew B.; Hamstra, Daniel A.; Kabolizadeh, Peyman; Gowans, Kate L.; Chen, Peter Y.
Abstract: Background: Atypical teratoid/rhabdoid tumors (AT/RTs) are rare aggressive central nervous system tumors. The use of radiation therapy (RT) remains controversial, especially for patients younger than three years of age. The purpose of the current investigation is to robustly analyze the impact of RT among pediatric AT/RT patients using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: SEER 18 Custom Data registries were queried for AT/RT (ICD‐0‐3 9508/3). A total of 190 pediatric AT/RT patients were identified, of whom 102 underwent surgery + chemotherapy and 88 underwent trimodality therapy. Univariate and multivariable analyses using Kaplan‐Meier and Cox proportional hazards regression modeling were performed. Propensity‐score matched analysis with inverse probability of treatment weighting was performed to account for indication bias. The landmark method was used to account for immortal time bias. Results: The majority of patients were <3 years old (75.8%). Patients <3 were more likely to be treated without RT as compared with older patients (62% vs 38%). Doubly robust MVA identified distant disease as a negative prognostic factor (HR 2.1, P = 0.003), whereas trimodality therapy was strongly protective (HR 0.39, P < 0.001). Infants (<1), toddlers (1‐2), and older children (3+) all benefited from trimodality therapy, with largest benefit for infants (HR 0.34, P = 0.02) and toddlers (HR 0.31, P < 0.001). Conclusion: The current study provides further evidence that trimodality therapy improves clinical outcomes among patients with AT/RT. This finding was most pronounced for younger patients; therefore, further studies are needed to confirm this finding in this vulnerable population.